Method for efficiently preparing porous copper foil and application thereof

CN117987907BActive Publication Date: 2026-10-30QINGHAI INST OF SALT LAKES OF CHINESE ACAD OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410168507.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-06
Publication Date
2026-10-30
Estimated Expiration
2044-02-06

AI Technical Summary

Technical Problem

多孔铜箔由锂电铜箔制备得到,其在锂离子电池充放电循环过程中具有大存储空间、高比表面积和减小体积膨胀等优异的结构优势,被广泛用于二次电池的负极集流体,然而,由于铜箔的厚度小、质地柔软和可变性,合理设计和高效制造3D多孔铜箔仍然是一个巨大的挑战

Benefits of technology

[0013]本发明提供的高效制备方法在络合剂电解液体系的基础上,使用添加剂两性嵌段聚合物,可以在短时间内形成数量多、孔径均匀、刻蚀完全、高比表面积的多孔铜箔,同时,铜箔边缘未被溶解,边缘清晰,完整性较好。同时,该方法操作简单,可塑性强,制备得到的多孔铜箔有望在二次电池领域广泛应用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117987907B_ABST
    Figure CN117987907B_ABST
Patent Text Reader

Abstract

The application discloses a kind of high-efficiency preparation methods and application of porous copper foil.The high-efficiency preparation method includes: providing complexing agent electrolyte system, the complexing agent electrolyte system includes complexing agent and additive, the complexing agent includes sodium potassium tartrate and EDTA salt, and the additive includes amphoteric block polymer;With copper foil as working electrode, the working electrode, counter electrode and complexing agent electrolyte system are constructed into electrochemical system, power electrolysis is carried out, and copper foil is electrochemically oxidized and etched to generate micron-sized holes on the surface of copper foil, and porous copper foil is prepared.The high-efficiency preparation method of the application can form a large number of porous copper foils with uniform pore size, complete etching and high specific surface area in a short time based on the complexing agent electrolyte system, while the edges of the copper foil are not dissolved, the edges are clear, and the integrity is good, which is expected to be widely used in the field of secondary batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for preparing copper foil, specifically to an efficient method for preparing porous copper foil and its application, belonging to the field of copper foil preparation technology. Background Technology

[0002] With the rapid rise of the new energy industry, lithium-ion batteries are developing towards smaller size and higher energy density, which means that the demand for lithium-ion battery copper foil is becoming increasingly prominent. As the negative electrode current collector of secondary batteries, lithium-ion battery copper foil must have important indicators such as high specific area and high tensile strength. Porous copper foil is made from lithium-ion battery copper foil. It has excellent structural advantages such as large storage space, high specific surface area and reduced volume expansion during the charge and discharge cycle of lithium-ion batteries, and is widely used as the negative electrode current collector of secondary batteries. However, due to the small thickness, soft texture and variability of copper foil, the rational design and efficient manufacturing of 3D porous copper foil remains a huge challenge. At present, the traditional methods for preparing porous copper foil mainly include powder sintering, dealloying, hydrogen bubble template, sol-gel method and other commonly used methods. However, these preparation methods are complicated and costly, which not only limits the application fields of porous copper foil, but also makes it difficult to achieve large-scale production. At the same time, the method of preparing porous copper foil by electrochemical etching is simple to operate and more conducive to wide-ranging use. The use of additives in the plating solution is an effective means to improve the performance of porous copper foil.

[0003] However, the porous copper foil prepared using existing electrochemical etching technology has incomplete pore etching, uneven pore size, and requires a relatively longer time to obtain a relatively uniform porous structure, which greatly limits its application. Summary of the Invention

[0004] The main objective of this invention is to provide an efficient method for preparing porous copper foil, thereby overcoming the shortcomings of the prior art.

[0005] Another object of the present invention is to provide a porous copper foil with high specific surface area and uniform pore size, and its applications.

[0006] To achieve the above-mentioned objectives, the present invention adopts the following technical solution:

[0007] This invention provides an efficient method for preparing porous copper foil, comprising:

[0008] A complexing agent electrolyte system is provided, the complexing agent electrolyte system comprising a complexing agent and an additive, the complexing agent comprising sodium tartrate and EDTA salt, and the additive comprising an amphoteric block polymer;

[0009] Using copper foil as the working electrode, an electrochemical system is constructed by the working electrode, the counter electrode, and the complexing agent electrolyte system. Electrolysis is performed by passing an electric current through the system to electrochemically oxidize and etch the copper foil, thereby generating micron-sized pores on the surface of the copper foil to produce a porous copper foil.

[0010] The present invention also provides a porous copper foil prepared by the aforementioned preparation method, wherein the porous copper foil has uniform micron-sized pores.

[0011] This invention also provides the application of the porous copper foil in the preparation of secondary batteries.

[0012] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0013] The efficient preparation method provided by this invention, based on a complexing agent electrolyte system, uses an amphoteric block polymer as an additive to form numerous porous copper foils with uniform pore size, complete etching, and high specific surface area in a short time. Simultaneously, the copper foil edges remain undissolved, exhibiting clear edges and good integrity. Furthermore, this method is simple to operate, highly adaptable, and the resulting porous copper foils are expected to have wide applications in the field of secondary batteries. Attached Figure Description

[0014] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0015] Figure 1 This is a schematic diagram of the reaction process for preparing porous copper foil using an efficient preparation method in a typical embodiment of the present invention;

[0016] Figure 2a , Figure 2b and Figure 2c This is a SEM image of the porous copper foil prepared in Example 1 of the present invention;

[0017] Figure 3a and Figure 3b This is a schematic diagram of the pore distribution and pore size of the porous copper foil obtained in Embodiment 1 of the present invention.

[0018] Figure 4a , Figure 4b , Figure 4c and Figure 4d This is a microstructure diagram of the copper foil prepared in Comparative Example 1. Detailed Implementation

[0019] In response to the shortcomings of existing technologies, the inventors of this invention, through long-term research and extensive practice, have proposed the technical solution of this invention, which is mainly a method for efficiently preparing porous copper foil in a short time. In a dual negative electrode system, the copper foil is subjected to electrochemical anodic oxidation treatment in an electrolyte to generate micron-sized pores on its surface.

[0020] The following will further explain the technical solution, its implementation process, and its principles. However, it should be understood that within the scope of this invention, the above-mentioned technical features of this invention and the technical features specifically described below (in embodiments) can be combined with each other to form new or preferred technical solutions. Due to space limitations, they will not be described in detail here.

[0021] As one aspect of the technical solution of this invention, the efficient preparation method of porous copper foil includes:

[0022] A complexing agent electrolyte system is provided, the complexing agent electrolyte system comprising a complexing agent and an additive, the complexing agent comprising sodium tartrate and EDTA salt, and the additive comprising an amphoteric block polymer;

[0023] Using copper foil as the working electrode, an electrochemical system is constructed by the working electrode, the counter electrode, and the complexing agent electrolyte system. Electrolysis is performed by passing an electric current through the system to electrochemically oxidize and etch the copper foil, thereby generating micron-sized pores on the surface of the copper foil to produce a porous copper foil.

[0024] In some preferred embodiments, the amphoteric block polymer may include any one or a combination of two of polyether F127, polyether P123, etc., but is not limited thereto. The amphoteric block polymer used in this invention is an amphiphilic surfactant, which can bind to metal ions through electrostatic or hydrogen bonding forces, thereby promoting the reaction.

[0025] Furthermore, the EDTA salt may be an EDTA-2Na salt, but is not limited thereto.

[0026] The preparation mechanism of this invention lies in the following: based on an electrolyte system using sodium tartrate and EDTA salt as complexing agents, amphoteric block polymers such as F127 and P123 are used as additives. This allows for the rapid formation of a porous structure with clear and uniform pore sizes on the copper foil surface, efficiently producing porous copper foils with high specific surface area and uniform pore size. On the one hand, it can produce porous copper foils with a large number of pores while ensuring the overall integrity of the copper foil. On the other hand, the prepared porous copper foil has uniform pore size, clear edges, complete etching, and a high specific surface area. Compared with existing processes, this invention has a high degree of innovation.

[0027] In some preferred embodiments, the concentration of the additive in the complexing agent electrolyte system is 1~500 mg / L.

[0028] In some preferred embodiments, the concentration ratio of sodium tartrate to EDTA salt in the complexing agent electrolyte system is 1:1 to 5:1.

[0029] In some preferred embodiments, the efficient preparation method of the porous copper foil includes: using the copper foil as the working electrode, and setting two counter electrodes on both sides of the working electrode to form a dual negative electrode system, thereby constructing the electrochemical system. Based on an electrolyte system using sodium tartrate and EDTA salt as complexing agents, this invention uses amphoteric block polymers such as F127 and P123 as additives. Under set electrochemical parameters, the copper foil is used as the anode (i.e., the working electrode), and an inert platinum electrode is used as the cathode, simultaneously forming an electrochemical three-electrode system with the electrolyte. Anodic electrochemical oxidation is performed on the copper foil to generate a porous structure with clear edges and uniform particle size on its surface in a short time.

[0030] Furthermore, the counter electrode comprises any one of titanium or an inert metal with an anti-corrosion coating on its surface, wherein the inert metal includes, but is not limited to, gold, platinum, etc.

[0031] In some preferred embodiments, the process conditions for the electrochemical oxidation etching treatment include: a temperature of 0–80°C, an electrolysis time of 10–600 s, and a current density of 10–1000 mA / cm². 2 .

[0032] As one of the more preferred implementation schemes, please refer to Figure 1 The reaction diagram illustrates a highly efficient method for preparing porous copper foil, which specifically includes the following steps:

[0033] Step 1: Use copper foil as the working electrode and titanium, gold, platinum or other inert metals with anti-corrosion coating as the counter electrode. The counter electrode is on both sides of the working electrode, forming a double negative electrode system with two negative electrodes.

[0034] Step 2: Use a mixture of potassium sodium tartrate and EDTA-2Na as the electrolyte;

[0035] Step 3: Add surfactants, amphoteric block polymers F127 and P123, to the electrolyte. The concentration of the additives is between 1-500 mg / L.

[0036] Step 4: Porous copper foil is prepared by anodic oxidation in an electrolyte by controlling conditions such as current magnitude, electrolysis time, and additive concentration. The temperature is 0–80 °C, the electrolysis time is 10–600 s, and the current density is 10–1000 mA / cm².2 .

[0037] In summary, the preparation method of the present invention is simple to operate and highly malleable. It can form a large number of porous copper foils with uniform pore size and complete etching in a short time. At the same time, the edges of the copper foil are not dissolved and have good integrity. This porous copper foil is expected to be widely used in the field of secondary batteries.

[0038] Another aspect of the present invention provides a porous copper foil prepared by the aforementioned preparation method, the porous copper foil having uniform micron-sized pores.

[0039] Furthermore, the pore size of the porous copper foil is 7~15 μm.

[0040] Furthermore, the porosity of the porous copper foil is 10% to 40%.

[0041] Another aspect of the present invention provides the wide application of the porous copper foil prepared above in the field of secondary batteries.

[0042] To make the objectives, technical solutions, and applications of this invention clearer, the technical solutions of this invention will be further described in detail below with reference to several preferred embodiments and accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention. The implementation conditions used in the following embodiments can be further adjusted according to actual needs; implementation conditions not specified are generally conditions in conventional experiments.

[0043] Example 1

[0044] A dual negative electrode system was formed using a 6 μm thick lithium-ion copper foil as the working electrode and platinum as the counter electrode. The electrolyte consisted of EDTA-2Na (0.18 mol / L) and potassium sodium tartrate (5:1). 5 mg / L of F127 was added to this electrolyte. The reaction temperature was 25 °C, the reaction time was 30 s, and the current density was set at 250 mA / cm². 2 The obtained sample, after washing and drying, becomes the prepared porous copper foil product.

[0045] Please see Figure 2a , Figure 2b and Figure 2c The image shown is a SEM image of the microstructure of the porous copper foil obtained in this embodiment. Figure 3a and Figure 3bThis is a schematic diagram showing the pore distribution and pore size of the porous copper foil obtained in Example 1.

[0046] Example 2

[0047] A dual negative electrode system was formed using a 6μm thick lithium-ion copper foil as the working electrode and a platinum sheet as the counter electrode. The electrolyte consisted of EDTA-2Na (0.18 mol / L) and potassium sodium tartrate (3:1). 5 mg / L of P123 was added to the electrolyte. The reaction temperature was 25℃, the reaction time was 30 s, and the current density was set to 250 mA / cm². 2 The obtained sample, after washing and drying, becomes the prepared porous copper foil product.

[0048] Example 3

[0049] A dual negative electrode system was formed using a 6 μm thick lithium-ion copper foil as the working electrode and platinum as the counter electrode. The electrolyte consisted of EDTA-2Na (0.18 mol / L) and potassium sodium tartrate (2:1 ratio). 1 mg / L of F127 was added to this electrolyte. The reaction temperature was 30 °C, the reaction time was 30 s, and the current density was set at 250 mA / cm². 2 The obtained sample, after washing and drying, becomes the prepared porous copper foil product.

[0050] Example 4

[0051] A dual negative electrode system was formed using a 6 μm thick lithium-ion copper foil as the working electrode and a titanium metal with an anti-corrosion coating as the counter electrode. The electrolyte consisted of EDTA-2Na (0.18 mol / L) and potassium sodium tartrate (1:1 ratio). 500 mg / L of F127 was added to this electrolyte. The reaction temperature was 30 °C, the reaction time was 30 s, and the current density was set to 250 mA / cm². 2 The obtained sample, after washing and drying, becomes the prepared porous copper foil product.

[0052] Example 5

[0053] A dual negative electrode system was formed using a 6 μm thick lithium-ion copper foil as the working electrode and gold as the counter electrode. The electrolyte consisted of EDTA-2Na (0.18 mol / L) and potassium sodium tartrate (5:1). 5 mg / L of F127 was added to this electrolyte. The reaction temperature was 30 °C, the reaction time was 10 s, and the current density was set to 1000 mA / cm². 2 The obtained sample, after washing and drying, becomes the prepared porous copper foil product.

[0054] Example 6

[0055] A dual negative electrode system was formed using a 6 μm thick lithium-ion copper foil as the working electrode and platinum as the counter electrode. The electrolyte consisted of EDTA-2Na (0.18 mol / L) and potassium sodium tartrate (4:1). 10 mg / L of F127 was added to this electrolyte. The reaction temperature was 0 °C, the reaction time was 600 s, and the current density was set to 100 mA / cm². 2 The obtained sample, after washing and drying, becomes the prepared porous copper foil product.

[0056] Example 7

[0057] A dual negative electrode system was formed using a 6 μm thick lithium-ion copper foil as the working electrode and platinum as the counter electrode. The electrolyte consisted of EDTA-2Na (0.18 mol / L) and potassium sodium tartrate (1:1 ratio). 50 mg / L of P123 was added to this electrolyte. The reaction temperature was 80 °C, the reaction time was 20 s, and the current density was set to 10 mA / cm². 2 The obtained sample, after washing and drying, becomes the prepared porous copper foil product.

[0058] Tests showed that the porous copper foils obtained in Examples 2-7 had pore sizes ranging from 7 to 15 μm and porosities ranging from 10% to 40%.

[0059] Comparative Example 1

[0060] The difference between this embodiment and Embodiment 1 is that F127 was not added.

[0061] The microscopic image of the copper foil obtained in this comparative example is as follows: Figures 4a-4d As shown, when copper foil is electrochemically oxidized using a complexing agent electrolyte alone without the addition of F127, the etching of holes on the surface of the prepared copper foil is not complete and the particle size is uneven under the same conditions.

[0062] In addition, the inventors of this case also conducted experiments with other raw materials, process operations, and process conditions described in this specification, referring to the aforementioned embodiments, and obtained relatively ideal results in all cases.

[0063] It should be understood that the examples described above are merely illustrative of the technical concept and features of the present invention, intended to enable those skilled in the art to understand the content of the present invention and implement it accordingly, and should not be used to limit the scope of protection of the present invention. All equivalent transformations or modifications made according to the spirit and essence of the present invention should be covered within the scope of protection of the present invention.

Claims

1. A highly efficient method for preparing porous copper foil, characterized in that, include: A complexing agent electrolyte system is provided, the complexing agent electrolyte system comprising a complexing agent and an additive, the complexing agent comprising sodium potassium tartrate and EDTA salt, the additive comprising an amphoteric block polymer, the amphoteric block polymer being selected from any one or a combination of two of F127 and P123; Using copper foil as the working electrode, an electrochemical system is constructed by the working electrode, the counter electrode, and the complexing agent electrolyte system. Electrolysis is performed by passing an electric current through the system to electrochemically oxidize and etch the copper foil, thereby generating micron-sized pores on the surface of the copper foil to produce a porous copper foil.

2. The efficient preparation method of porous copper foil according to claim 1, characterized in that: The concentration of the additive in the complexing agent electrolyte system is 1~500 mg / L.

3. The efficient preparation method of porous copper foil according to claim 1, characterized in that: The concentration ratio of sodium tartrate to EDTA salt in the complexing agent electrolyte system is 1:1 to 5:

1.

4. The efficient preparation method of porous copper foil according to claim 1, characterized in that, include: Using copper foil as the working electrode, two counter electrodes are respectively placed on both sides of the working electrode to form a double negative electrode system, thus constructing the electrochemical system described above.

5. The efficient preparation method of porous copper foil according to claim 1 or 4, characterized in that: The counter electrode comprises either titanium or an inert metal with an anti-corrosion coating on its surface.

6. The efficient preparation method of porous copper foil according to claim 5, characterized in that: The inert metal includes either gold or platinum.

7. The efficient preparation method of porous copper foil according to claim 1, characterized in that, The electrochemical oxidation etching process conditions include: temperature of 0~80 ℃, electrolysis time of 10~600 s, and current density of 10~1000 mA / cm². 2 .

Citation Information

Patent Citations

  • Method for preparing porous copper foil by electroetching in hydrosol system

    CN115182032A